Predasi dan Respons Fungsional Lima Spesies Coccinellidae sebagai Predator Potensial Wereng Batang Coklat (Nilaparvata lugens) - Fatikhul Karim; Wiwin Windriyanti; Hery Nirwanto (EduInovasi: Journal of Basic Educational Studies, 2026)
Brown planthopper (Nilaparvata lugens) is a major rice pest that can significantly reduce yields, even leading to crop failure, therefore a biological control strategy is needed by utilizing natural predators.This study tested the predation ability and functional responsse of five Coccinellidae species (Micraspis lineata, Micraspis discolor, Cheilomenes sexmaculata, Coccinella transversalis, and Coelophora inaequalis) against brown planthopper imago at five levels of prey density using a factorial Completely Randomized Design with 48 hour observation. This study analyzed the ability to prey, predation rate, attack rate, handling time, and the type of functional responsse through regression based on Holling Disc Equation modeling. The results showed significant differences between species (p < 0.05) with C. transversalis being the most efficient predator with the highest attack rate (0.6861) and the lowest handling time (0.0311), followed by M. lineata (a = 0.6615; Th = 0.0798), while C. inaequalis was the predator with the lowest effectiveness. All species showed a type III functional responsse with the quadratic model having the highest R². These results indicate that C. transversalis and M. lineata are potential predators as biological control agents for brown planthopper in rice agroecosystems.